ANALISIS KELAYAKAN USAHA TERNAK KELINCI (Kelompok Ternak Kelinci “Sumber Lestari-- Desa Sumber Kecamatan Sanankulon Kabupaten Blitar) - Rosyda Fajarini (AVES: Jurnal Ilmu Peternakan, 2016)
The study was started on May 1, 2012 through June 15, 2012 in the rabbit animal group "SUMBER LESTARI" Sumber Village Sanankulon subdistrict Blitar District. The purpose of this Thesis are to (1) determine the expenditure and revenue of the rabbit animal group "SUMBER LESTARI", (2) determine the feasibility of the rabbit animal group "SUMBER LESTARI".The material obtained from this study were in the rabbit animal group "SUMBER LESTARI" Sumber Village Sanankulon subdistrict Blitar District by the number of respondents as many as 17 people. The research method used in this thesis research is descriptive method that is trying to tell the current problem solving based on the data, so it presents research data, analyze and interpret.The results of this study were (1) The amount of expenditures and receipts of the rabbit animal group "SUMBER LESTARI" is an average of Rp. 1.971.529/year for expenses while receiving an average of Rp. 2.126.659/year, (2) The the rabbit animal group "SUMBER LESTARI" worth the try. It can be seen from the R/C by an average of 1.074 and the value of B /C average of 0.074.Keywords : rabbit, feasibility, recipts.